The Influence of Financial Literacy, Business Capital, and Time Management on MSME Performance - Nadia Christy; Miar Miar; Wiwin Zakiah (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic development, yet many struggle to achieve sustainable performance due to limited managerial capacity and resources. This study investigates the influence of financial literacy, business capital, and time management on the performance of MSMEs. Using a quantitative approach, data from 100 MSME respondents were analyzed using SPSS to examine relationships and test hypotheses through multiple linear regression and statistical analysis. The results indicate that all three independent variables have a significant effect on MSMEs performance both individually and collectively. Among them, financial literacy and time management were identified as the most influential predictors, while business capital had a relatively smaller effect. The model’s determination coefficient (R² = 0.586) suggests that approximately 58.6% of the variation in MSMEs performance can be explained by these variables. This study demonstrates that managerial capacity, especially financial literacy and time management, has a greater effect on MSMEs’ success than capital alone, suggesting policies should focus on capacity-building rather than just funding. This study contributes to the strategic development of competency-based MSMEs empowerment models tailored to regional contexts.